PENILAIAN RISIKO IKLIM PADA SISTEM PERTANIAN EKOSISTEM LAHAN RAWA PASANG SURUT (STUDI KASUS DI DELTA TELANG I, DELTA TELANG II DAN DELTA AIR SALEH, BANYUASIN, SUMATERA SELATAN) (CLIMATE RISK ASSESMENT ON AGRICULTURAL SYSTEM IN SWAMP AREAS ... - . Suciantini; . Impron; Rizaldi Boer (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2008)
The characteristics of swampland areas are different from agricultural land of Java, mainly in water availability. In swampland ecosystems there are unique environmental conditions. To assess risks of climate, mainly in climate change, we must assess about capacity and adaptation strategy. From treasure of related institution and interview with farmers,its had been known about climate impact on farming systems application, rainfall pattern and water availability. This paper aims to assess risks of climate on farming systems, application of adaptation strategy to reduce risks of climate and probability to provide of planting pattern alternative in the future in swampland areas (tidal marsh) in Delta Telang I, Delta Telang II and Delta Air Saleh, Banyuasin, South Sumatera.